Diurnal variations in physical performances related to football in young trained soccer players - Chtourou, H.; Hammouda, O.; Souissi, H.; Chamari, K.; Chaouachi, A.; Souissi, N. (Asian Journal of Sports Medicine, 2012)
Purpose: This study investigated the effects of time-of-day on aerobic and anaerobic performances during the Yo-Yo, repeated sprint ability (RSA) and the Wingate tests in young soccer players.